PEMBERDAYAAN IBU RUMAH TANGGA GMIT JEMAAT MARTHOMAS MANULAI II KOTA KUPANG MELALUI BUDIDAYA AYAM KUB UNTUK PENINGKATAN GIZI DAN EKONOMI KELUARGA - Detha, Annytha Ina Rohi; Ndaong, Nemay Anggadewi; Foeh, Nancy Diana Ferderika Katerina (Universitas Nusa Cendana, 2025)
This community service activity aimed to empower families of GMIT Jemaat Marthomas Kupang through the cultivation of Kampung Unggul Balitbangtan (KUB) chickens as an effort to improve family nutrition and economic resilience. The activity was carried out on Sunday, April 13, 2025, using the Asset-Based Community Development (ABCD) approach. The primary targets of this program were housewives within the congregation, who were recognized as key agents in managing family nutrition and household finances. Through the ABCD approach, the local assets and potential of the congregation were identified and optimized to build independence in KUB chicken farming. The activities included education on poultry management, distribution of KUB chicks, and technical mentoring. The outcomes showed increased knowledge and skills among the housewives in raising KUB chickens, along with a growing awareness of the importance of animal protein in fulfilling family nutritional needs. This program is expected to be sustainable and to have a positive impact on improving the overall quality of life of the congregation.